Analysis of Determinants of Competitive Advantage and its Impact on Marketing Performance in Retail Business in Batam City - Cuandra, Fendy; Willien Agustian; Lady; Lily Purwianti (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: This study aims to analyze the influence of innovation, social media, market orientation, entrepreneurial orientation, and competitor orientation on marketing performance in retail businesses, with competitive advantage as a mediating variable. Method; Data was collected through a survey involving ritel companies in various sectors in the Batam city area, by distributing questionnaires to 350 people in various retail companies in the city of Batam is a research method used to test the relationship between variables. Results; The results showed that social media innovation, market orientation, entrepreneurial orientation, and competitor orientation significantly affect marketing performance, both directly and indirectly through competitive advantage. Competitive advantage acts as a factor that strengthens the influence of these variables on marketing performance. Conclusion; This research suggests that ritel businesses should continue to innovate, maintain the right market orientation, and focus on entrepreneurship and understanding of competitors to create a sustainable competitive advantage